Badiou and the Political Condition - Constantinou, Marios (Critical Connections : CRCO, 2021)
Unpacks the diverse intellectual legacies woven into Badiou's work on contemporary polemics and political interventionsThe 11 essays in this volume, including a new piece by Badiou himself, reflect the formative traditions that shape the background of his political thought. They intervene critically and evaluate the present state of Badiou's work, while also breaking new ground and creating new thresholds of political thought.The contributors are a range of established scholars and rising theorists of the Badiou-effect. Each engages with the critical question of 'how to transmit the exception' politically. at the intersection of contemporary anti-imperial polemics and debates that strike at the heart of the post-modern condition (Lyotard), deconstruction (Derrida), psychoanalysis (Lacan - Zizek), biopolitics (Hardt and Negri) and pedagogy (Rancière).Key FeaturesAddresses the entire range of Badiou's political interventions and polemicsIncludes a chapter by Badiou: 'From Logic to Anthropology: Affirmative Dialectics'Investigates the anti-imperialist edge of his philosophy of truthBrings together his opposition to parliamentary politics with his trenchant critique of biopolitics